DEVELOPMENT OF COLLEGE STUDENT WORKSHEET BASED E-LEARNING THROUGH EDMODO TO MAXIMIZE THE RESULTS LEARNING AND MOTIVATION - Nasrullah, Anton; Marlina, Mira (Journal on Mathematics Education, 2019)
The objective of the study was to develop a college student worksheet using Edmodo as a learning support tool and to know the effectiveness of peer tutor learning model applied in the learning of economic mathematics on motivation and attitude. Research used for quantitative approach and quasi-experiment method to collect data applying test and questionnaire. The sample in the study is a second-year student enrolled in a college in Serang - Banten. The sample comes from two classes. One class was used for the control group of 29 students; one for the exploratory group of 40 students. In the control group, students were taught only in a personal learning environment using peer tutor models whereas experimental groups studied through peer tutor models in the classroom were supported by student worksheet learning using Edmodo. The findings show that college student worksheet's use is better than traditional learning. That is, students in the experimental group not only outperformed them in the control group in the learning outcomes, but they also showed a higher learning motivation. Although students in both groups did not differ in their attitudes toward peer tutor models, students in the experimental group expressed positive attitudes toward Edmodo.